EDUKASI KEMANDIRIAN FINANCIAL MELALUI KEWIRAUSAHAAN PADA PANTI YATIM YAUMA - Yusbardini, Yusbardini (Transpublika Publisher, 2023)
Entrepreneurship is one way that is considered powerful enough for people to live independently and survive in the midst of difficult situations like this. Entrepreneurship is important for an individual as a provision for a future that will be faced with intense competition and challenges. More than that, entrepreneurship is also important for an individual to optimize his ability and financial independence. In line with this, there is a need for early entrepreneurship training to community groups, especially children. Underprivileged orphans are no exception. Most orphans have difficulty accessing education and skills training. Therefore, this training activity is aimed at orphans managed by the Yauma Orphanage Foundation in West Bekasi. Especially, for those who are already in high school / MA. The aim is to prepare them to live independently after being released from the foundation. This training is conducted through online media. The PKM Entrepreneurship material consists of: the basics of entrepreneurship, starting a business with light capital, and utilizing gadgets as support for entrepreneurial activities. This activity went well and smoothly, participants assessed that all material delivery could be understood, participants could also know and understand well what entrepreneurship is, the capital needed.